Bathymetry of Southeast Greenland From Oceans Melting Greenland (OMG) Data. Issue 20 (21st October 2019) - An, Lu; Rignot, Eric; Chauche, Nolwenn; Holland, David M.; Holland, Denise; Jakobsson, Martin; Kane, Emily; Wood, Michael; Klaucke, Ingo; Morlighem, Mathieu; Velicogna, Isabella; Weinrebe, Wilhelm; et al.
Abstract: Southeast Greenland has been a major participant in the ice sheet mass loss over the last several decades. Interpreting the evolution of glacier fronts requires information about their depth below sea level and ocean thermal forcing, which are incompletely known in the region. Here, we combine airborne gravity and multibeam echo sounding data from the National Aeronautics and Space Administration's Oceans Melting Greenland (OMG) mission with ocean probe and fishing boat depth data to reconstruct the bathymetry extending from the glacier margins to the edges of the continental shelf. We perform a three‐dimensional inversion of the gravity data over water and merge the solution with a mass conservation reconstruction of bed topography over land. In contrast with other parts of Greenland, we find few deep troughs connecting the glaciers to the sources of warm Atlantic Water, amidst a relatively uniform, shallow (350 m) continental shelf. The deep channels include the Kangerlugssuaq, Sermilik, Gyldenløve, and Tingmiarmiut Troughs. Key Points: A multisensor approach resolves the bathymetry on the continental shelf and glacial fjords of southeast Greenland Few deep or complex networks of troughs connect the glaciers to the sources of warm Atlantic Water; that is, access to ocean heat is limited The new bathymetry helps interpret the past and recent evolution of southeast Greenland glaciers and contribution to sea level rise